2 METODA SIGNIFIKAN PENDONGKRAK POSISI DOMAIN PADA MESIN PENCARI - Gunawan, Ibnu (Jurnal Informatika, 2009)
Based on data from the Internet survey from independent institutions in the United States named pewinternet as on 6 August 2008 by Deborah Fallow stating that using search engine is the second largest activity of the Internet user after e-mail, so it can not be denied that the main key to the success of a website is how the website domain listed first on the search results of a search engine. One way to ensure this is to have a high SEO score. This makes the writer is interested to conduct experiments on the relationship SEO score and ranking of a domain in search engines. Experiments carried out in an e-business lecture class, where there are 5 groups with their own domain and then we optimized their SEO. The results obtained were surprising, it turns out that high SEO score does not guarantee a high ranking and the top of the list of a search engine. This journal will explain in detail how it is done.